Effect of Electrode Configuration and Impulse Strength on Airway Patency in Neurostimulation for Obstructive Sleep Apnea. (17th April 2021) - Pawlak, Dominik; Bohorquez, Dominique; König, Inke R.; Steffen, Armin; Thaler, Erica R.
Abstract : Objectives/Hypothesis: Hypoglossal nerve stimulation (HNS) has gained increasing interest for the treatment of patients with obstructive sleep apnea (OSA). Drug‐induced sleep endoscopy (DISE) can both exclude improper airway collapse patterns and visualize airway changes under stimulation. Stimulation outcome effects depend on the impulse voltage and electric field resulting from the electrode configuration of the implanted device. The effects of various combinations of voltage and electric field on DISE airway patterns in contrast to awake endoscopy are unknown. Study Design: Cohort study. Methods: During therapy adjustment about 6 months after implantation, patients underwent a DISE and awake endoscopy with 100% and 125% of functional voltage in three typical electrode configurations (+ – +, o – o, − – −). All videos were analyzed by two separate persons for the opening of the airway at velum, tongue base, and epiglottis level. Results: Thirty patients showed typical demographic data. The opening effects were visible in all patients, but there were changes between different electrode configurations. Several demographic or therapeutic aspects such as obesity, OSA severity, or prior soft palate surgery were associated with changes arising from different electrode configurations, but none resulted in a consistently better airway opening. Conclusions: In patients with poor results during the therapy adjustment, electric configuration changes can improve airway patency—an independent variable from increasing voltage. As these effects can only be seen in awake endoscopy or DISE, both endoscopies with live stimulation may be considered in cases with insufficient improvement in apnea–hypopnea index after initiation of HNS therapy. Level of Evidence: Prospective case series; level 4. Laryngoscope, 131:2148–2153, 2021